Guinea pig auditory nerve response triggered by a high density electrode array - Jolly, C N; Clopton, B M; Spelman, F A; Lineaweaver, S K (Medical progress through technology, 1997)
The electrically evoked potential in the auditory nerve is measured when the cochlear is stimulated with a high density electrode array whose microcontacts (20 x 160 microns) are placed close to the nerve cells. Threshold range from 8 to 35 microA with the stimulating electrodes near the spiral ganglion cells. A multi-pole technique for restricting the spread of current with electrical stimulation of the cochlea is tested using neural recording in deafened guinea pigs. The ground based quadrupolar electrode driving configuration has thresholds for neural activation only slightly greater than monopolar stimulation when the electrode contacts are placed less than 50 microns from the neurons. During simultaneous stimulation the monopole and the ground based quadrupolar modes tend to generate similar growth functions (magnitude and latency). The electrode interactions are generally factorial, which means that the algebraic sum of the responses (magnitude growth functions) produced by 2 distinct electrodes is less than when the same 2 electrodes are stimulated simultaneously.